[Yuchengco Center for East Asia sponsored the lecture by Ralph Cossa] - Cossa, Ralph (Animo Repository, 1997)
Yuchengco Center for East Asia sponsored the lecture, Revitalized United States-Japan Relations and the Impact on Japan's Asia-Pacific Neighbors by Ralph Cossa, Executive Director of Pacific Forum, an affiliate of the Center for Strategic and International Studies (CSIS) in the US. Pacific Forum CSIS is a think tank on political security, economic and environmental issues.